Charge transport mechanism in copper phthalocyanine thin films with and without traps. Issue 86 (1st December 2017) - Rani, Varsha; Sharma, Akanksha; Kumar, Pramod; Singh, Budhi; Ghosh, Subhasis
Abstract : We investigate the charge transport mechanism in copper phthalocyanine thin films with and without traps. We find that the density of interface states at the grain boundaries can decide the mechanism of charge transport in organic thin films. Abstract : We investigate the charge transport mechanism in copper phthalocyanine thin films with and without traps. Previously, charge transport in polycrystalline thin films has been widely described by the multiple trapping and release (MTR) model, without emphasizing the origin of the traps. In this work, polycrystalline organic thin films with and without traps have been grown by engineering different growth conditions. We find that the density of interface states at the grain boundaries can decide the mechanism of charge transport in organic thin films and completely different charge transport mechanisms can be observed in thin films with and without traps.